An evaluation of corrosion processes affecting copper-coated nuclear waste containers in a deep geological repository. (May 2021) - Hall, David S.; Behazin, Mehran; Jeffrey Binns, W.; Keech, Peter G.
Abstract: Permanent disposal of high level nuclear waste in containers that employ steel as a structural element and copper as a corrosion barrier material is a favoured design concept in several countries. This review considers possible corrosion processes that can affect these packages and demonstrates the methodology used to calculate corrosion depth over package service life in a Canadian deep geological repository environment. Four corrosion sub-allowances are considered: oxic corrosion due to trapped oxygen, radiation-influenced corrosion, anoxic aqueous corrosion, and microbiologically-influenced corrosion. Additional corrosion and container failure mechanisms are discussed, including stress corrosion cracking, creep ductility and fracture, hydrogen embrittlement, coating debonding for copper-coating technologies, and failure at weld regions. Several areas for future study are suggested. Exact corrosion allowances will depend on site-specific geological and groundwater properties, especially the far-field sulphide concentration. For the generic Canadian site conditions described, the expected depth of corrosion is evaluated at 270 μm in 1, 000, 000 years. Including additional, highly conservative considerations for each possible corrosion reaction, the maximum corrosion damage is 1.2 mm in 1, 000, 000 years. This is significantly less than the 3 mm coating thickness in the Canadian used fuel container design or the 25–50 mm thickness of copper in dual walled vessels.